Case Report: Abiraterone in brain metastases from prostate cancer - Peres, Tobias; Aeppli, Stefanie; Fischer, Stefanie; Rothermundt, Christian (Frontiers in Oncology, 2025)
BackgroundProstate carcinoma (PC) is the most common cancer in men worldwide. However, brain metastases (BM) from prostate cancer are extremely rare events, usually in the later course of the disease. There is no established standard of care treatment for this situation. The efficacy of androgen synthesis inhibitor abiraterone in BM from PC is unknown.CaseWe herein report the case of an 83-year-old patient with metastatic hormone-sensitive PC who had multiple BM at primary diagnosis, clinically manifesting with dizziness, ataxia, and unsteady gait. Combination of abiraterone and androgen deprivation therapy showed exceptional sustained cerebral tumor response. After 12 months of treatment, the patient is asymptomatic with an excellent performance status.ConclusionSymptomatic BM from PC is a rarity but can show sustained response to abiraterone and androgen deprivation therapy. After comprehensive literature search, there is no comparable case published to date.